Rethinking strategic purchasing for the financial sustainability of Indonesia's National Health Insurance or Jaminan Kesehatan Nasional (JKN): An opinion - Wiky Fhalyang (Health Economics Insights Journal, 2026)
Indonesia's National Health Insurance or Jaminan Kesehatan Nasional (JKN), launched in 2014 and now covering more than 95% of the population, is the largest single-payer health insurance scheme in the world. However, its rapid expansion of population coverage has been shadowed by chronic financial deficits that have required repeated government injections and contribution increases. This Opinion advances the thesis that JKN's sustainability problem has been misframed as primarily a revenue problem, when the more decisive and underused lever is the way BPJS Kesehatan spends the money it pools—that is, its purchasing function. I argue that JKN still purchases largely passively: it contracts providers on a near-automatic basis, pays primary care through blunt capitation, and hospitals through case-based the Indonesian Case Base Groups (INA-CBG) tariffs that are weakly linked to quality or value, and under-uses Health Technology Assessment (HTA), claims analytics, and selective contracting. Drawing on the strategic-purchasing literature and evidence from Indonesia and comparable middle-income countries, I contend that shifting from passive to strategic purchasing—value-based benefit design, selective and performance-linked contracting, outcome-oriented provider payment, and data- and HTA-informed decisions—can simultaneously restrain expenditure growth, improve quality, and protect equity. Revenue reforms, including contribution adequacy and earmarked tobacco excise, remain necessary but are insufficient without purchasing reforms. I set out the trade-offs, political economy constraints, and a concrete sequenced reform agenda. Strategic purchasing, not perpetual bailouts, is the JKN's most credible path to financial sustainability and meaningful universal health coverage.